Legal Analysis of Embezzlement in Office in Committing Corruption in Decision No. 2182 K / Pid.Sus/2019 - Efrianto, Gatot; Gayo, Sabela (International Asia Of Law and Money Laundering, 2026)
Embezzlement in office is a corruption modus operandi that threatens the country's financial stability through abuse of authority by state officials. Objective: This study analyzes the legal construction of embezzlement in office as a crime of corruption as well as the consideration of judges in the Supreme Court Decision No. 2182 K/Pid.Sus/2019. Method: normative juridical approach is used by reviewing legislation and court decisions through literature studies, as well as descriptive qualitative analysis of primary and secondary legal materials. Result: the verdict proved that the defendant's actions meet the elements of embezzlement in office and corruption in the presence of substantial state financial losses due to abuse of authority. The judge takes into account the aspect of causality between office and state losses, as well as applies proportionate sanctions taking into account aggravating and mitigating factors.